Efficacy of jute-glass hybrid laminate composite wrapping under flexural loading - Achmad Jusuf Zulfikar; Siswo Pranoto; Din Aswan A. Ritonga; Johannes J.B. Butar Butar; Bincar Orlando Simanjuntak (JTTM : Jurnal Terapan Teknik Mesin, 2024)
The demand for sustainable engineering materials has catalyzed interest in hybrid composites that combine natural fibers like jute with synthetic fibers such as E-glass. This study investigates the flexural strength of jute/E-glass/epoxy hybrid composite laminates under different stacking sequences, employing the ANOVA method to analyze their mechanical performance. The materials, including jute fabric, E-glass fabric, and epoxy resin, were arranged in various configurations and tested for flexural strength following ASTM D790 standards. The results indicated significant variability, with the GJGJ configuration exhibiting the highest average flexural strength of 71.20 MPa, while the GJG configuration had the lowest at 26.33 MPa. The ANOVA analysis confirmed a statistically significant effect of laminate configuration on flexural strength (F = 6.41, p = 0.004). These findings underscore the critical role of laminate arrangement in enhancing the mechanical properties of hybrid composites. The superior performance of the GJGJ configuration suggests that alternating layers of jute and E-glass fibers can effectively distribute stress and enhance load-bearing capacity. Conversely, suboptimal configurations like GJG demonstrated lower performance, highlighting the importance of strategic fiber arrangement. This research contributes to the development of optimized hybrid composites for various engineering applications, providing valuable insights into the interplay between natural and synthetic fibers within a composite matrix. The study's conclusions support the broader use of hybrid composites in industries such as automotive, construction, and aerospace, where material sustainability and performance are paramount. Future research should explore further optimization of stacking sequences and volume fractions of fibers, as well as investigate other mechanical properties such as tensile and impact strength, to fully realize the potential of hybrid composites in advanced engineering applications